Biodegradable curcumin-nanoclay films for extending shrimp shelf-life and freshness - Kalpani Y. Perera; Sneha Sabu Mathew; Luana de S.C. Carnaval; Dileswar Pradhan; Amit K. Jaiswal; Swarna Jaiswal (Current Research in Food Science)
Preserving food freshness is fundamental for minimizing waste. Intelligent packaging offers valuable information, enhances safety, and improves food quality during storage and transit. This study aimed to develop biodegradable, intelligent food packaging for shrimp using curcumin (Cur), gelatin (Gel), sodium alginate (SA), and nanoclay (NC) to enhance food safety and extend shelf life. The films with 1 % NC-Cur exhibited a 3.46-fold increase in UV barrier properties compared to the control, although Cur reduced transparency. Mechanical testing showed that films containing 0.5 % NC-Cur achieved optimal tensile strength (38.6 ± 30.9 MPa). The water contact angle (WCA) increased to 84.12 ± 3.14°, indicating enhanced hydrophobicity, while solubility decreased significantly. The films demonstrated pH-responsive color changes (yellow to brick red) and improved antioxidant activity, with 1 % NC-Cur scavenging 35.55 % radicals compared to 15.10 % in the control. Biodegradation studies confirmed complete degradation within 30 days, although films with higher NC levels showed slower curcumin migration. After six days, shrimp stored at 4 °C exhibited a yellow-to-orange color change due to microbial growth and pH fluctuations. Packaging with NC-Cur extended shrimp shelf life by two days. These findings demonstrate the potential of NC, Cur, Gel, and SA-based films for intelligent, eco-friendly packaging that enhances food quality, delays spoilage, and reduces environmental impact.